The Evolution of Health Care Utilisation and Costs for Inflammatory Bowel Disease Over Ten Years. (27th March 2019) - Pillai, Nadia; Dusheiko, Mark; Maillard, Michel H; Rogler, Gerhard; Brüngger, Beat; Bähler, Caroline; Pittet, Valérie E H; ,
Abstract: Background and Aims: Inflammatory bowel disease [IBD] places an economic strain on health systems due to expensive pharmaceutical therapy, risk of hospitalisation and surgery, and long-term monitoring. The evolving treatment guidelines advocate rapid scale-up to biologic agents in order to improve health outcomes and quality of life. This study evaluated changes in health care utilisation and expenditures for IBD in Switzerland over time. Methods: We extracted clinical, patient, and resource consumption data from the Swiss IBD Cohort Study between 2006 and 2016. Average unit costs for IBD-related events were derived from Swiss claims data and pharmaceutical price lists. We used multivariate regression, controlling for patient-level characteristics, to estimate trends and determinants of direct and indirect costs and resource utilisation. Results: We included 2365 adults diagnosed with Crohn's disease [CD; N = 1353] and ulcerative colitis [UC; N = 1012]. From 2006–16, mean health care expenditures per patient per year were 9504 euros [70% drugs, 23% inpatient, 7% outpatient] for CD and 5704 euros [68% drugs, 22% inpatient, 10% outpatient] for UC. Health care costs increased by 7% [CD] and 10% [UC] per year, largely due to rising pharmaceutical expenditures driven by increased biologic agent use. Inpatient, outpatient, and indirect costs fluctuated and did not offset increased pharmaceutical costs. Disease characteristics were important predictors of costs. Conclusions: Increased expenditure for IBD was marked by a shift towards greater pharmaceutical management over the past decade. This study highlights the need to identify cost-effective treatment strategies in the face of increased uptake and expenditures associated with innovative treatments.